Improving Housing Status Quo - PHANG, Sock Yong (Institutional Knowledge at Singapore Management University, 2013)
On home ownership and upgrading, PM Lee Hsien Loong has reaffirmed the Government's objective to make home ownership more affordable for all first-time buyers, especially low-income earners, through increasing the amounts of targeted housing grant subsidies. He spelt out the desired outcomes of housing affordability policy through his detailed matching of Housing Board flat type with household incomes.